(untitled) (CIPEEX, 2025)
One of the most common and frequent traumatic dental injuries is crown fractures, especially in children and adolescents. Aesthetic and functional rehabilitation is always a challenge for the dental surgeon. When the fragment is intact or with little loss of structure, bonding with the adhesive technique is the preferred minimally invasive conservative option. Objective: To report a clinical case of tooth fragment reattachment using the adhesive technique in a patient who presented with a fractured maxillary anterior tooth, with the fragment still present. Clinical case report: Patient ARCCA, male, sought emergency care at the UNIEVANGÉLICA Dental Clinic, accompanied by his mother, as he was a minor. The mother reported that her son "fell on the floor and broke his front tooth; I found the piece and put it in a cup with saline solution." On intraoral examination, an oblique fracture of the distal angle of tooth 21 was observed. The remaining tooth and the fragment were evaluated and found to be in perfect condition. After radiographic and sensitivity testing, fragment reattachment using only an adhesive system was indicated, as the fragment was perfectly adapted to the remaining tooth. A follow-up was performed after one week, and no changes in color or sensitivity were detected. Conclusions: Tooth fragment reattachment using the adhesive technique demonstrated excellent results in rapidly and effectively restoring both aesthetics and function.